Early Loading of Single-Piece Implant for Partially Edentulous Posterior Arch: A Prospective One-Year Case Report - Amol Beldar; Manohar L. Bhongade; Girish Byakod; Chandrashekar Buregoni (Case Reports in Dentistry)
Implant therapy is now well established, and there is an increasing need for shorter rehabilitation time. Original prerequisites of osseointegration have been reassessed to satisfy continuously increasing patient's expectation of reduced treatment time, improved esthetics, and increased comfort. Shorter healing time may be appropriate in some circumstances, and examples of early loading have been reported in animal and human studies. However, to date there are insufficient data to determine a universally acceptable opinion on early loading of implants for single-tooth replacement. This case report involves early loading, combined with construction of a restoration, inserted directly after 6 weeks of implant surgery and followup of one year.